Chestnut-shaped silicon-tin-based composite negative electrode material as well as preparation method and application thereof
By adopting a two-layer coated chestnut structure and porous structure design in the silicon-tin-based composite negative electrode material, the problem of low capacity retention rate in the existing technology is solved, and efficient electrochemical performance and stability are achieved.
Patent Information
- Application Number
- CN202411659346.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-24
AI Technical Summary
The existing silicon-tin-based composite anode material has low capacity retention during charging and discharging, which limits its application in lithium-ion batteries.
Adopt two layers of chestnut -shaped structure design, the nuclear is a silicon tin -based material, the first layer is carbon nanotuba doped carbon layer, the second layer is an amorphous nitrogen doped carbon layer, and through specific preparation methods. Including phenolic resin aggregation reactions and thermal treatment, a porous structure is formed to relieve volume expansion.
It significantly improves the 200 cycle capacity and internal resistance performance of the silicon tin -based compound negative material, and ensure the high efficiency and stability of the battery.
Smart Images

Figure CN119361667A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium ion battery composite negative electrode materials, and in particular relates to a chestnut-shaped silicon-tin-based composite negative electrode material, a preparation method and application thereof. Background Art
[0002] The limited supply of fossil fuels and global warming are promoting the development of electric vehicles to replace gasoline-fueled vehicles. Lithium-ion batteries, which are widely used in portable electronic devices, are a promising source of power for electric vehicles. At present, graphite anodes are still the commercial mainstream, but their low theoretical specific capacity of 372 mAh / g limits their application and development in the new generation of high energy density lithium-ion batteries. Therefore, the development of alternative materials is imminent, among which silicon and tin stand out due to their higher theoretical capacity, lower potential and abundant reserves, but their huge volume expansion (about 300%) during the charge and discharge process hinders their application. Therefore, a large number of researchers have tried to improve the carbonaceous matrix and non-carbonaceous matrix from the aspects of nano-sizing of intrinsic materials, construction of composite materials, and construction of three-dimensional structures, and have achieved certain results.
[0003] CN113782732A introduces a single-atom tin-based composite carbon material and a preparation method thereof. Tin salt, phenolic substances, aldehyde substances and solvents are mixed, and a phenolic resin polymerization reaction is carried out; the obtained product is subjected to solid-liquid separation, and the obtained solid portion is carbonized to obtain the single-atom tin-based composite carbon material. The discharge capacity in the first week is 1170-1430mAh / g, which is 3-4 times the capacity of graphite, but the capacity after 100 cycles is only 388-478mAh / g, and the capacity retention rate after 100 cycles is less than 40%. This method greatly improves the capacity performance of the carbon and tin composite, but the low capacity retention rate limits its performance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defect of low capacity retention rate of silicon-tin-based composite negative electrode materials in the prior art during charge and discharge. Therefore, a chestnut-shaped silicon-tin-based composite negative electrode material, a preparation method and application thereof are provided. The silicon-tin-based composite negative electrode material of the present invention satisfies one or more of the following effect advantages: (1) high discharge capacity in the first cycle; (2) high capacity retention rate after 200 cycles; (3) low internal resistance.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The present invention provides a silicon-tin-based composite negative electrode material, which contains 20%-32% silicon, 40%-55% tin, 10%-20% carbon, 5%-11% oxygen and 0.5%-1.5% nitrogen; the percentage is the percentage of each element in the total mass of the silicon-tin-based composite negative electrode material;
[0007] The silicon-tin-based composite negative electrode material is a chestnut-shaped structure with two layers of coating, the core is a silicon-tin-based material, the first layer is a carbon nanotube-doped carbon layer; the second layer is an amorphous nitrogen-doped carbon layer; there is a cavity between the first layer and the second layer.
[0008] In some embodiments, the silicon content is 21%-29%, for example, 25.5%, 25.3%, 27.8%, 26.3%, 25.1%, 25.4%, 28.3%, 25.8%, 24.7%, 26.1%, 25.9%, 27.3% or 27.7%.
[0009] In some embodiments, the content of tin element is 44%-52%, for example 49.7%, 49.5%, 46.6%, 49.9%, 51.9%, 49.4%, 45.9%, 49.8%, 47.9%, 50.2% or 50.1%.
[0010] In some embodiments, the carbon content is 13%-17%, for example, 16%, 15.1%, 15.4%, 14.2%, 16.2%, 17%, 14.8%, 15.9%, 13.05%, 13.7% or 13.1%.
[0011] In some embodiments, the content of oxygen element is 6%-9.5%, for example 7.8%, 8.9%, 9.1%, 8.3%, 6.9%, 8.1%, 7.9%, 8.2%, 8.5%, 8% or 7.7%.
[0012] In some embodiments, the nitrogen content is 0.7%-1.2%, for example, 0.8%, 1%, 0.9%, 1.1%, 0.7%, 1.2% or 0.95%.
[0013] In some embodiments, the silicon-tin-based composite negative electrode material further comprises hydrogen element, and the content of the hydrogen element may be 0.1%-0.4%, for example 0.2%.
[0014] In some embodiments, the D of the silicon-tin based composite negative electrode material 50 It is 100 nm to 180 nm, preferably 120 nm to 160 nm, for example 130 nm, 140 nm, 160 nm, 150 nm, 135 nm, 155 nm, 145 nm, 125 nm or 148 nm.
[0015] In some embodiments, the pore size of the silicon-tin based composite negative electrode material is 10 nm-22 nm, preferably 14 nm-19 nm, for example 16.2 nm, 14.8 nm, 16.7 nm, 15.9 nm, 18.1 nm, 18.4 nm, 17.6 nm, 17.3 nm, 15.8 nm, 19.2 nm or 17.8 nm.
[0016] In some embodiments, the electrical conductivity of the silicon-tin-based composite negative electrode material is 2×10^4S / m-4×10^4S / m, preferably 2.3×10^4S / m-3.7×10^4S / m, for example, 2.4×10^4S / m, 3.1×10^4S / m, 2.8×10^4S / m, 3.4×10^4S / m, 3.7×10^4S / m, 3.5×10^4S / m, 2.7×10^4S / m, 2.3×10^4S / m, 3.3×10^4S / m, 2.9×10^4S / m or 2.6×10^4S / m.
[0017] In some embodiments, the charge transfer internal resistance of the silicon-tin-based composite negative electrode material is 22Ω-36Ω, preferably 25Ω-34Ω, for example, 25.7Ω, 28.1Ω, 30.8Ω, 33.8Ω, 26.8Ω, 29.7Ω, 30.7Ω, 32.8Ω, 29.8Ω, 29.9Ω, 25.8Ω, 27.9Ω or 33.1Ω.
[0018] In some embodiments, the silicon-tin-based composite negative electrode material is composed of 21%-29% silicon, 44%-52% tin, 13%-17% carbon, 6%-9.5% oxygen, 0.7%-1.2% nitrogen and 0.1%-0.4% hydrogen.
[0019] In some embodiments, the silicon-tin-based composite negative electrode material is any of the following:
[0020] Option 1: 25.5% silicon, 49.7% tin, 16% carbon, 7.8% oxygen, 0.8% nitrogen and 0.2% hydrogen;
[0021] Option 2: 25.3% silicon, 49.5% tin, 15.1% carbon, 8.9% oxygen, 1% nitrogen and 0.2% hydrogen;
[0022] Option 3: 27.8% silicon, 46.6% tin, 15.4% carbon, 9.1% oxygen, 0.9% nitrogen and 0.2% hydrogen;
[0023] Option 4: 26.3% silicon, 49.9% tin, 14.2% carbon, 8.3% oxygen, 1.1% nitrogen and 0.2% hydrogen;
[0024] Option 5: 25.1% silicon, 51.9% tin, 15.1% carbon, 6.9% oxygen, 0.8% nitrogen and 0.2% hydrogen;
[0025] Option 6: 25.4% silicon, 49.4% tin, 16.2% carbon, 8.1% oxygen, 0.9% nitrogen and 0.2% hydrogen;
[0026] Option 7: 28.3% silicon, 45.9% tin, 17% carbon, 7.9% oxygen, 0.7% nitrogen and 0.2% hydrogen;
[0027] Option 8: 25.8% silicon, 49.7% tin, 14.8% carbon, 8.3% oxygen, 1.2% nitrogen and 0.2% hydrogen;
[0028] Option 9: 24.7% silicon, 49.8% tin, 15.9% carbon, 8.2% oxygen, 1.2% nitrogen and 0.2% hydrogen;
[0029] Scheme 10: 26.1% silicon, 47.9% tin, 16.2% carbon, 8.5% oxygen, 1.1% nitrogen and 0.2% hydrogen;
[0030] Scheme 11: 25.9% silicon, 51.9% tin, 13.05% carbon, 8% oxygen, 0.95% nitrogen and 0.2% hydrogen;
[0031] Scheme 12: 24.7% silicon, 49.9% tin, 16.2% carbon, 7.9% oxygen, 1.1% nitrogen and 0.2% hydrogen;
[0032] Scheme 13: 27.3% silicon, 50.2% tin, 13.7% carbon, 7.7% oxygen, 0.9% nitrogen and 0.2% hydrogen;
[0033] Scheme 14: 27.7% silicon, 50.1% tin, 13.1% carbon, 7.9% oxygen, 1% nitrogen and 0.2% hydrogen.
[0034] In some embodiments, the silicon-tin-based composite negative electrode material is prepared by the following method, which includes the following steps (1) to (4):
[0035] Step (1): in the presence of an alkali, a solvent and a nitrogen source, a silicon-tin-based material, an alkylated carbon nanotube, a phenolic compound and an aldehyde compound are subjected to a phenolic resin polymerization reaction, and the product is heat-treated to obtain a carbon nanotube-doped carbon-coated porous silicon-deposited porous tin dioxide material (silicon-tin-based@carbon nanotube-doped carbon);
[0036] Wherein, the mass ratio of the alkylated carbon nanotube to the silicon-tin-based material is (0.12-0.43): 1;
[0037] The mass ratio of the phenolic compound to the silicon-tin-based material is (0.013-0.047): 1;
[0038] The mass ratio of the aldehyde compound to the silicon-tin-based material is (3.7-12.9): 1;
[0039] In the silicon-tin-based material, the mass ratio of silicon element to tin element is 1:(1.5-2.3);
[0040] Step (2): coating the silicon-tin-based@carbon nanotube-doped carbon with a NiO layer to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO;
[0041] Step (3): reacting the silicon-tin-based@carbon nanotube-doped carbon@NiO in a solvent in the presence of a surfactant, a nitrogen source and an initiator, and heat-treating the product to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon;
[0042] Wherein, the mass ratio of the nitrogen source to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (3-1): 1;
[0043] Step (4): In the presence of an acid, removing NiO from the silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon to obtain the silicon-tin-based composite negative electrode material.
[0044] In some embodiments, in step (1), the base is a strong base or a weak base; the strong base may be sodium hydroxide; the weak base may be sodium carbonate or sodium citrate; the base is preferably sodium carbonate.
[0045] In some embodiments, in step (1), the solvent is a conventional solvent for phenolic resin polymerization in the art, preferably water, such as deionized water.
[0046] In some embodiments, in step (1), the nitrogen source is a conventional nitrogen source for phenolic resin polymerization in the art, preferably one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobis(ethylbutyronitrile) and pyrrole, such as p-nitroaniline.
[0047] In some embodiments, in step (1), the phenolic compound is a conventional phenolic compound used in the art for phenolic resin polymerization reaction, preferably resorcinol.
[0048] In some embodiments, in step (1), the aldehyde compound is a conventional aldehyde compound used in the art for phenolic resin polymerization reaction, preferably formaldehyde.
[0049] In some embodiments, in step (1), the phenolic resin polymerization reaction may also be carried out in the presence of a surfactant, wherein the surfactant is preferably a cationic surfactant, preferably a quaternary ammonium salt cationic surfactant, such as one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, for example, hexadecyltrimethylammonium bromide or dialkyldimethylammonium chloride.
[0050] In some embodiments, in step (1), the mass ratio of the base to the silicon-tin-based material is (0.0002-0.009):1, for example, 0.00029:1 or 0.00024:1.
[0051] In some embodiments, in step (1), the mass ratio of the nitrogen source to the silicon-tin-based material is (0.00024-0.0034):1, for example, 0.0011:1 or 0.001:1.
[0052] In some embodiments, in step (1), the mass ratio of the alkylated carbon nanotubes to the silicon-tin-based material is 0.23:1 or 0.2:1.
[0053] In some embodiments, in step (1), the mass ratio of the phenolic compound to the silicon-tin-based material is 0.03:1 or 0.027:1.
[0054] In some embodiments, in step (1), the mass ratio of the aldehyde compound to the silicon-tin-based material is 7.7:1 or 6.6:1.
[0055] In some embodiments, in step (1), in the silicon-tin-based material, the mass ratio of silicon element to tin element is 1:(1.6-2.1), for example, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2.
[0056] In some embodiments, in step (1), when the phenolic resin polymerization reaction is carried out in the presence of a surfactant, the mass ratio of the surfactant to the silicon-tin-based material is (0.017-0.069):1, for example, 0.047:1 or 0.04:1.
[0057] In some embodiments, in step (1), the reaction temperature of the phenolic resin polymerization reaction is 80-100°C, preferably 90°C.
[0058] In some embodiments, in step (1), the reaction time of the phenolic resin polymerization reaction is related to the reaction scale and is not specifically limited. The reaction time is preferably 2-10 hours, for example 6 hours.
[0059] In some embodiments, in step (1), the temperature of the heat treatment is 600-700°C, preferably 650°C.
[0060] In some embodiments, in step (1), the heat treatment time may be the conventional time for such heat treatment in the art, which is related to the reaction scale. The heat treatment time is preferably 2-40 h, such as 10 h.
[0061] In some embodiments, in step (1), the phenolic resin polymerization reaction comprises the following steps: mixing a mixture containing a surfactant, alkylated carbon nanotubes and a solvent with a nitrogen source, a phenolic compound, an aldehyde compound, a base and a silicon-tin-based material, and performing a phenolic resin polymerization reaction at 80-100° C.;
[0062] The mass ratio of the alkylated carbon nanotube to the silicon-tin-based material is (0.12-0.43): 1;
[0063] The mass ratio of the phenolic compound to the silicon-tin-based material is (0.013-0.047): 1;
[0064] The mass ratio of the aldehyde compound to the silicon-tin-based material is (3.7-12.9): 1;
[0065] In the silicon-tin-based material, the mass ratio of silicon element to tin element is 1:(1.5-2.3).
[0066] In some embodiments, in step (1), the silicon-tin-based material is prepared by the following steps: drying and heat treating a sol containing tin and a surfactant, and introducing a silicon source gas by atomic layer deposition to prepare the silicon-tin-based material.
[0067] The tin is an inorganic salt of tin, such as tin tetrachloride.
[0068] The surfactant is a cationic surfactant, preferably a quaternary ammonium salt cationic surfactant, such as one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, and for example cetyltrimethylammonium bromide or dialkyldimethylammonium chloride.
[0069] The device used in the atomic layer deposition method may be a Beneq TFS 200 atomic layer deposition device.
[0070] The silicon source gas is one or more of tetraethoxysilane, methylsilane, ethylsilane and silane, preferably methylsilane.
[0071] The flow rate of the silicon source gas is 50-100 mL / min, preferably 60 mL / min.
[0072] The working temperature of the atomic layer deposition with the silicon source gas introduced is 100-300°C, preferably 200°C or 250°C.
[0073] The duration of the atomic layer deposition with the silicon source gas introduced is 24-48 hours, preferably 28 hours.
[0074] The number of cycles of atomic layer deposition with the silicon source gas introduced is 50-200, preferably 80 or 120.
[0075] The drying temperature is 80-100°C.
[0076] In some embodiments, in step (1), the alkylated carbon nanotubes are prepared by the following steps: Step A: preparing carbon nanotubes from graphite by an arc method;
[0077] Step B: Carboxylating the carbon nanotubes in the presence of an acid and potassium permanganate to obtain carboxylated carbon nanotubes;
[0078] Step C: In the presence of alkyl alcohol or alkyl amine, the carboxylated carbon nanotubes are subjected to an alkylation reaction to obtain alkylated carbon nanotubes.
[0079] The alkyl alcohol may be a lower alcohol or a higher alcohol. The lower alcohol may be methanol, ethanol or propanol. The higher alcohol may be lauryl alcohol or stearyl alcohol. The alkyl alcohol is preferably lauryl alcohol.
[0080] The alkylamine is preferably octadecylamine.
[0081] The alkylated carbon nanotubes are lauryl alkylated carbon nanotubes or octadecyl alkylated carbon nanotubes.
[0082] In some embodiments, step (2) comprises the following steps: reacting silicon-tin-based@carbon nanotube-doped carbon in a solvent in the presence of a surfactant, a nickel salt, an initiator and a base, and heat-treating the product to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO.
[0083] The solvent is water, such as deionized water.
[0084] The surfactant is a cationic surfactant, preferably a quaternary ammonium salt cationic surfactant, such as one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, and for example cetyltrimethylammonium bromide or dialkyldimethylammonium chloride.
[0085] The nickel salt is an inorganic salt of nickel, such as nickel acetate.
[0086] The initiator is a persulfate, preferably one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate, such as potassium persulfate.
[0087] The base is an inorganic base, such as aqueous ammonia, more preferably 10% (w / w) aqueous ammonia.
[0088] The temperature of the heat treatment is 350-600°C, preferably 400°C.
[0089] Preferably, the step (2) comprises the following steps: mixing a mixture containing silicon-tin-based@carbon nanotube-doped carbon and a surfactant, a mixture containing a nickel salt and an initiator, and a base, reacting at room temperature, collecting the product, drying, and heat treating to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO.
[0090] In some embodiments, in step (3), the solvent is water, such as deionized water.
[0091] In some embodiments, in step (3), the surfactant is an anionic surfactant, preferably one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate; preferably hexadecyltrimethylammonium p-toluenesulfonate.
[0092] In some embodiments, in step (3), the nitrogen source is a 5-6 membered heterocyclic compound containing 1, 2 or 3 N atoms; preferably a 5-6 membered heterocyclic compound containing 1 N atom; for example, pyridine and / or pyrrole.
[0093] In some embodiments, in step (3), the initiator is a persulfate, preferably one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate, such as potassium persulfate.
[0094] In some embodiments, in step (3), the mass ratio of the nitrogen source to the silicon-tin-based@carbon nanotube-doped carbon@NiO is 2:1.
[0095] In some embodiments, in step (3), the mass ratio of the surfactant to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (0.03-0.1):1, preferably 0.08:1.
[0096] In some embodiments, in step (3), the mass ratio of the initiator to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (2-6.5):1, preferably 3.5:1.
[0097] In some embodiments, in step (3), the reaction temperature of the reaction is -5-10°C, preferably 0-5°C.
[0098] In some embodiments, in step (3), the temperature of the heat treatment may be 550-850°C; preferably 700°C.
[0099] In some embodiments, in step (3), the heat treatment may be performed under an inert atmosphere, preferably under an argon atmosphere.
[0100] In some embodiments, in step (3), the heat treatment time may be 3-10 hours, preferably 5 hours.
[0101] In some embodiments, step (3) comprises the following steps: mixing the silicon-tin-based@carbon nanotube-doped carbon@NiO, a surfactant, a nitrogen source and an initiator in a solvent, reacting at 0-5°C, collecting the product, drying, and heat treating to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon;
[0102] The mass ratio of the nitrogen source to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (3-1):1.
[0103] In some embodiments, in step (4), the acid is an inorganic acid, preferably one or more of hydrochloric acid, nitric acid and sulfuric acid, such as hydrochloric acid. The concentration of the hydrochloric acid is preferably 5 mol / L.
[0104] In some embodiments, step (4) may further include a washing and / or drying step. The washing may be washing with deionized water. The drying may be vacuum drying; the vacuum drying temperature is preferably 80°C.
[0105] The present invention also provides a method for preparing the silicon-tin-based composite negative electrode material, which comprises the following steps (1) to (4):
[0106] Step (1): in the presence of an alkali, a solvent and a nitrogen source, a silicon-tin-based material, an alkylated carbon nanotube, a phenolic compound and an aldehyde compound are subjected to a phenolic resin polymerization reaction, and the product is heat-treated to obtain a carbon nanotube-doped carbon-coated porous silicon-deposited porous tin dioxide material (silicon-tin-based@carbon nanotube-doped carbon);
[0107] Wherein, the mass ratio of the alkylated carbon nanotube to the silicon-tin-based material is (0.12-0.43): 1;
[0108] The mass ratio of the phenolic compound to the silicon-tin-based material is (0.013-0.047): 1;
[0109] The mass ratio of the aldehyde compound to the silicon-tin-based material is (3.7-12.9): 1;
[0110] In the silicon-tin-based material, the mass ratio of silicon element to tin element is 1:(1.5-2.3);
[0111] Step (2): coating the silicon-tin-based@carbon nanotube-doped carbon with a NiO layer to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO;
[0112] Step (3): reacting the silicon-tin-based@carbon nanotube-doped carbon@NiO in a solvent in the presence of a surfactant, a nitrogen source and an initiator, and heat-treating the product to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon;
[0113] Wherein, the mass ratio of the nitrogen source to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (3-1): 1;
[0114] Step (4): removing NiO from the silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon in the presence of an acid to obtain the silicon-tin-based composite negative electrode material;
[0115] The steps (1), (2), (3) and (4) are as described in any one of the above items.
[0116] The present invention also provides an application of the silicon-tin-based composite negative electrode material in a battery.
[0117] The present invention also provides a battery, which comprises the silicon-tin-based composite negative electrode material.
[0118] Explanation of terms
[0119] In the present invention, the term "room temperature" refers to 15-40°C, for example 25°C.
[0120] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0121] The reagents and raw materials used in the present invention are commercially available.
[0122] The positive and progressive effects of the present invention are that the silicon-tin-based composite negative electrode material of the present invention has one or more of the following advantages: (1) effectively alleviating the volume expansion of silicon and tin materials; (2) making the best use of the capacity of the silicon-tin-based material to obtain excellent electrochemical performance (for example, rate performance, capacity, and cycle stability); (3) increasing the diffusion pathway of lithium ions so that the electrolyte can quickly and evenly infiltrate the interior of the material, thereby improving the rate performance after multi-layer coating.
[0123] The method for preparing the silicon-tin-based composite negative electrode material of the present invention has one or more of the following advantages: (1) the porous tin pore structure in the prepared negative electrode material is complete; (2) while alleviating the volume expansion of the silicon and tin materials, the lithium ion expansion rate is enhanced, thereby improving the rate performance; (3) low cost; and (4) high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0124] Figure 1 A schematic diagram of the cycle performance of a composite negative electrode material prepared based on the method of the present invention;
[0125] Figure 2 Schematic diagram of the rate performance of the composite negative electrode material prepared based on the method of the present invention. DETAILED DESCRIPTION
[0126] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0127] Example 1
[0128] (1) Preparation of lauryl alkylated carbon nanotubes
[0129] The artificial graphite sieve (after sieving D 50 15-30 μm), passed into a ball mill at a speed of 600 r / min for 7 h to obtain D 50 The nanoparticles were added with 250 mL of 8% (w / w) hydrochloric acid and repeatedly washed with acid to fully remove the metal impurities. Then, they were repeatedly washed with water and ethanol until the pH was neutral, and then dried at 80 ° C for 24 h to obtain black powder. The black powder was mixed with iron powder (D 5050-80μm) was prepared into a graphite electrode at a mass ratio of 96:4 (prepared with reference to CN118343745A). The graphite electrode was fixed in a vacuum arc discharge device as anode and cathode, and argon gas was introduced to keep the vacuum degree at 0.2Mpa. The arc discharge time was 2min at a current of 99A to obtain crude carbon nanotubes. 250mL of 8% (w / w) hydrochloric acid was added again for repeated acid washing to fully remove the metal impurities, and then rinsed repeatedly with water and ethanol until the pH was neutral, and then dried at 80-100℃ for 24h to obtain refined carbon nanotubes.
[0130] The purified carbon nanotubes (1.5 g) were added to 100 mL of a mixture of dilute sulfuric acid / potassium permanganate with a volume-to-mass ratio of 1 / 2.5 (the concentration of dilute sulfuric acid was 4.5 mol / L), and the temperature was 60 ° C. Ultrasonic stirring was performed for 1 h to obtain carboxylated carbon nanotubes (yield of about 95%). Subsequently, the carboxylated carbon nanotubes (8 g) were added to N, N-dimethylformamide (250 ml) and ultrasonically dispersed for 50 min. Subsequently, a mixture of lauryl alcohol and N, N'-dicyclohexylcarbodiimide with a mass ratio of 2:1 (1.5 g) was added to react. Finally, the mixture was separated by centrifugation and repeatedly washed with ethanol and distilled water. Finally, the product was vacuum dried at 80 ° C for 24 h to obtain lauryl carbon nanotubes.
[0131] (2) Preparation of porous silicon deposited porous tin dioxide materials
[0132] Tin tetrachloride (20.3 g, 78 mmol) was added to deionized water (135 mL), and the mixture was stirred for 20 min. Hexadecyl trimethyl ammonium bromide (0.22 g, 0.6 mmol) was then added, stirred evenly, and allowed to stand for 24 h to form a stable sol, which was then rinsed repeatedly with water and ethanol, dried at 80 °C under vacuum for 24 h, and then heat treated at 600 °C (3 °C / min) for 7 h to obtain porous tin dioxide. Subsequently, the porous tin dioxide was used as a substrate template and sent into a Beneq TFS 200 atomic layer deposition (ALD) device with a flow rate of 60 mL / min of methylsilane gas, the operating temperature was 200 °C, and the duration was 28 h. After 80 cycles, argon gas was used to purge the residual impurity gas after the cycle was stopped, and the silicon-deposited porous tin dioxide was obtained by quickly cooling to room temperature.
[0133] The prepared silicon-deposited porous tin dioxide is mixed with magnesium powder in a mass ratio of 1:5, placed in a tube furnace for heat treatment at a temperature of 600°C for 3-8 hours, with a heating rate of 2°C / min, and then treated with 6% (w / w) hydrochloric acid, followed by repeated rinsing with distilled water and ethanol, and dried in an oven at 80°C for 24 hours to obtain a porous silicon-deposited porous tin dioxide material (i.e., silicon-tin-based material).
[0134] (3) Preparation of porous tin dioxide materials doped with carbon nanotubes and carbon-coated porous silicon
[0135] Hexadecyltrimethylammonium bromide (0.164 g, 0.45 mmol) and lauryl carbon nanotubes (0.8 g) were mixed and ultrasonically dispersed for 45 min to make them uniformly distributed in deionized water (108 mL). Then, a mixture of p-nitroaniline (0.004 g, 0.03 mmol), resorcinol (0.11 g, 1 mmol), formaldehyde (27 g, 0.9 mol) and sodium carbonate (0.001 g, 0.01 mmol) was added and stirred continuously. Subsequently, the porous silicon deposited porous tin dioxide material (3.5 g) prepared in step (2) was added to obtain a surfactant-stabilized core-shell colloid. The surfactant-stabilized core-shell colloid was polymerized at 90 ° C for 6 h to obtain a gel polymer encapsulated by porous silicon deposited porous tin dioxide.
[0136] After drying, the material was heat treated at 650°C for 10 h in an argon atmosphere to obtain a carbon nanotube-doped carbon-coated porous silicon-deposited porous tin dioxide material (i.e., silicon-tin-based@carbon nanotube-doped carbon).
[0137] (4) Preparation of chestnut-shaped silicon-tin-based composite negative electrode materials
[0138] Silicon tin-based@carbon nanotube-doped carbon (0.2 g) was added to deionized water (50 mL) dissolved with hexadecyltrimethylammonium bromide (0.01 g, 0.027 mmol), stirred, and ultrasonicated for 50 min to obtain a silicon tin-based@carbon nanotube-doped carbon dispersion. Nickel acetate (0.2 g, 0.8 mmol) and potassium persulfate (0.1 g, 0.37 mmol) were dissolved in another 50 mL of distilled water. After complete dissolution, they were slowly added to the silicon tin-based@carbon nanotube-doped carbon dispersion. After stirring for 50 min, 20 mL of 10% (w / w) ammonia water was added. In an oil bath, stirred again at 25 ° C, and finally, the product was collected by centrifugation and dried in vacuum at 80 ° C for 24 h to obtain composite material A (silicon tin-based@carbon nanotube-doped carbon@NiOOH). The composite material A nanoparticles were heated at 400°C at a rate of 2°C / min in an inert atmosphere, kept at the constant temperature for 3 hours, and then rapidly cooled to obtain the precursor material B (silicon tin based@carbon nanotube doped carbon@NiO).
[0139] Dissolve hexadecyltrimethylammonium p-toluenesulfonate (8 mg, 0.018 mmol) in deionized water (250 mL); add precursor material B (0.1 g) and stir for 50 min; add pyrrole (0.2 mL) under ice bath conditions at 0-3°C and stir for another 50 min. Then, add distilled water (40 mL) dissolved with potassium persulfate (0.35 g, 1.29 mmol) and stir at a reaction temperature of 0-5°C for 24 h. After the reaction is completed, the product is collected by centrifugation, washed with distilled water and ethanol in turn to remove impurities, and dried in vacuum at 80°C for 24 h to obtain precursor C. Precursor C is calcined at 700°C in an argon atmosphere for 5 h and then rapidly cooled to obtain precursor material D (silicon tin base @ carbon nanotube doped carbon @ NiO @ amorphous nitrogen doped carbon).
[0140] The nickel oxide layer in the precursor material D was removed with hydrochloric acid (5 mol / L) and washed with deionized water to neutrality. Finally, vacuum dried at 80°C for 24 h to obtain the final product: chestnut-shaped silicon-tin-based composite negative electrode material (silicon-tin-based@carbon nanotube-doped carbon@cavity@amorphous nitrogen-doped carbon).
[0141] Example 2
[0142] The difference from Example 1 is that in step (1), the mass ratio of black powder to iron metal catalyst is 95:4.
[0143] Example 3
[0144] The difference from Example 1 is that the iron powder in step (1) is replaced by nickel powder (D 50 50-80μm).
[0145] Example 4
[0146] The difference from Example 1 is that the arc discharge time in step (1) is 5 minutes.
[0147] Example 5
[0148] The difference from Example 1 is that the lauryl alcohol in step (1) is replaced by octadecylamine.
[0149] Example 6
[0150] The difference from Example 1 is that 0.8 mmol of hexadecyltrimethylammonium bromide is added in step (2).
[0151] Example 7
[0152] The difference from Example 1 is that the first heat treatment temperature in step (2) is 650°C.
[0153] Example 8
[0154] The difference from Example 1 is that the atomic layer deposition operating temperature in step (2) is 250°C.
[0155] Example 9
[0156] The difference from Example 1 is that the number of atomic layer deposition cycles in step (2) is 120 times.
[0157] Example 10
[0158] The difference from Example 1 is that the second heat treatment temperature in step (2) is 700°C.
[0159] Embodiment 11
[0160] The difference from Example 1 is that the surfactant in step (3) is dialkyldimethylammonium chloride.
[0161] Example 12
[0162] The difference from Example 1 is that the amount of resorcinol in step (3) is 1.1 mmol.
[0163] Embodiment 13
[0164] The difference from Example 1 is that 4.1 g of porous silicon-deposited porous tin dioxide material (ie, silicon-tin-based material) is added in step (3).
[0165] Embodiment 14
[0166] The difference from Example 1 is that pyrrole is replaced by pyridine in step (4).
[0167] Comparative Example 1:
[0168] The difference from Example 1 is that only step (1) is included and only the artificial graphite on the sieve is obtained after ball milling.
[0169] Comparative Example 2:
[0170] The difference from Example 1 is that there is only step (2).
[0171] Comparative Example 3:
[0172] The difference from Example 1 is that the negative electrode material is pure nano silicon powder 75nm.
[0173] Comparative Example 4:
[0174] The difference from Example 1 is that no silicon deposition is performed in step (2).
[0175] Physical and chemical properties test:
[0176] After XRF testing, the mass content of elements in the chestnut-shaped silicon-tin-based composite negative electrode material synthesized by the present invention was tested by XRF method, and the sample was pre-treated by microwave digestion method. The chestnut-shaped silicon-tin-based composite negative electrode material prepared in each embodiment was pre-treated by mixing and grinding 2±0.05g of stearic acid and 6±0.5g of the sample to be tested, and then pressed into tablets, and then tested in Avio™200 equipment; test conditions: air pressure greater than 2MPa. The conductivity was measured by Orion Star TM The conductivity was measured by A212 benchtop meter at room temperature. The pore size was measured by POROLUX Cito instrument; the internal resistance was measured by electrochemical impedance spectroscopy (compacted density 1.65 g / cm 3 ) The physical and chemical results are shown in the following table.
[0177] Table 1
[0178]
[0180] The above-mentioned Examples 1-14 also contain 0.2% of hydrogen element.
[0181] Lithium-ion button cell battery testing:
[0182] The preparation method of the button cell used for testing the electrochemical performance is as follows: the battery negative electrode material prepared in the embodiment and the comparative example is mixed evenly with the conductive agent (KS-6), CMC, and SBR according to 95.5:1.5:1.5:1.5, and applied on the copper foil. The compaction density is 1.60g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte uses a mixture of 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, the separator is a PE / PP / PE composite film, and assembled into a button battery. The test conditions are: charge and discharge at a current density of 0.1C-3C, and the charging voltage is limited to 0.005-2V. The test results of the cycle performance (within 200 cycles and within 300 cycles) of Example 1 at a rate of 0.1C are shown as follows Figure 1 ; Example 1 performs rate performance (within 50 cycles) test results as shown Figure 2 and Table 2.
[0183] Table 2
[0184]
[0185] The rate capacity retention rate after 5 cycles* = equal to + capacity after 5 cycles / initial rate capacity*100.
[0186] according to Figure 1 It can be seen that at a rate of 0.1C, the capacity and efficiency data obtained after 300 cycles of charge and discharge, the capacity retention rate is still higher than 80% after 300 cycles, which shows that the material has excellent cycle performance.
[0187] according to Figure 2 As shown in Table 3, at a rate of 2C, the capacity retention rate can still reach 70%, indicating that the expansion of the silicon material has been greatly improved, and a stable capacity has been achieved. At the same time, the addition of porous structures and highly conductive tin-based and carbon-based materials further improves the poor rate performance of the silicon material.
[0188] The test results of the capacity and cycle performance (within 200 cycles) of Examples 1-14 at a rate of 0.1C are shown in Table 3.
[0189] Table 3
[0190]
[0191] The capacity retention rate of the composite material obtained by the present invention is maintained at more than 80% at a rate of 0.1C, indicating that the expansion of the silicon material has been greatly improved, and a stable capacity performance is obtained. At the same time, the addition of porous structures and high-conductivity tin-based and carbon-based materials further improves the poor rate performance of the silicon material.
Claims
1. A silicon-tin based composite negative electrode material, characterized in that: It contains 20%-32% silicon, 40%-55% tin, 10%-20% carbon, 5%-11% oxygen and 0.5%-1.5% nitrogen; the percentage is the percentage of each element in the total mass of the silicon-tin-based composite negative electrode material; The silicon-tin-based composite negative electrode material is a chestnut-shaped structure with two layers of coating, the core is a silicon-tin-based material, the first layer is a carbon nanotube-doped carbon layer; the second layer is an amorphous nitrogen-doped carbon layer; there is a cavity between the first layer and the second layer.
2. The silicon-tin based composite negative electrode material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The silicon content is 21%-29%, for example, 25.5%, 25.3%, 27.8%, 26.3%, 25.1%, 25.4%, 28.3%, 25.8%, 24.7%, 26.1%, 25.9%, 27.3% or 27.7%; (2) The tin content is 44%-52%, such as 49.7%, 49.5%, 46.6%, 49.9%, 51.9%, 49.4%, 45.9%, 49.8%, 47.9%, 50.2% or 50.1%; (3) The carbon content is 13%-17%, such as 16%, 15.1%, 15.4%, 14.2%, 16.2%, 17%, 14.8%, 15.9%, 13.05%, 13.7% or 13.1%; (4) The oxygen content is 6%-9.5%, for example, 7.8%, 8.9%, 9.1%, 8.3%, 6.9%, 8.1%, 7.9%, 8.2%, 8.5%, 8% or 7.7%; (5) The nitrogen content is 0.7%-1.2%, for example, 0.8%, 1%, 0.9%, 1.1%, 0.7%, 1.2% or 0.95%; (6) The silicon-tin-based composite negative electrode material further comprises hydrogen element; the content of the hydrogen element may be 0.1%-0.4%, for example 0.2%; (7) D of the silicon-tin based composite negative electrode material 50 100 nm to 180 nm, preferably 120 nm to 160 nm, for example 130 nm, 140 nm, 160 nm, 150 nm, 135 nm, 155 nm, 145 nm, 125 nm or 148 nm; (8) The pore size of the silicon-tin based composite negative electrode material is 10 nm to 22 nm, preferably 14 nm to 19 nm, for example, 16.2 nm, 14.8 nm, 16.7 nm, 15.9 nm, 18.1 nm, 18.4 nm, 17.6 nm, 17.3 nm, 15.8 nm, 19.2 nm or 17.8 nm; (9) The electrical conductivity of the silicon-tin based composite negative electrode material is 2×10^4S / m-4×10^4S / m, preferably 2.3×10^4S / m-3.7×10^4S / m, for example, 2.4×10^4S / m, 3.1×10^4S / m, 2.8×10^4S / m, 3.4×10^4S / m, 3.7×10^4S / m, 3.5×10^4S / m, 2.7×10^4S / m, 2.3×10^4S / m, 3.3×10^4S / m, 2.9×10^4S / m or 2.6×10^4S / m; and (10) the charge transfer internal resistance of the silicon-tin-based composite negative electrode material is 22Ω-36Ω, preferably 25Ω-34Ω, for example, 25.7Ω, 28.1Ω, 30.8Ω, 33.8Ω, 26.8Ω, 29.7Ω, 30.7Ω, 32.8Ω, 29.8Ω, 29.9Ω, 25.8Ω, 27.9Ω or 33.1Ω.
3. The silicon-tin based composite negative electrode material according to claim 1, characterized in that: The silicon-tin-based composite negative electrode material is composed of 21%-29% silicon, 44%-52% tin, 13%-17% carbon, 6%-9.5% oxygen, 0.7%-1.2% nitrogen and 0.1%-0.4% hydrogen. Preferably, the silicon-tin-based composite negative electrode material is any of the following: Option 1: 25.5% silicon, 49.7% tin, 16% carbon, 7.8% oxygen, 0.8% nitrogen and 0.2% hydrogen; Option 2: 25.3% silicon, 49.5% tin, 15.1% carbon, 8.9% oxygen, 1% nitrogen and 0.2% hydrogen; Option 3: 27.8% silicon, 46.6% tin, 15.4% carbon, 9.1% oxygen, 0.9% nitrogen and 0.2% hydrogen; Option 4: 26.3% silicon, 49.9% tin, 14.2% carbon, 8.3% oxygen, 1.1% nitrogen and 0.2% hydrogen; Option 5: 25.1% silicon, 51.9% tin, 15.1% carbon, 6.9% oxygen, 0.8% nitrogen and 0.2% hydrogen; Option 6: 25.4% silicon, 49.4% tin, 16.2% carbon, 8.1% oxygen, 0.9% nitrogen and 0.2% hydrogen; Option 7: 28.3% silicon, 45.9% tin, 17% carbon, 7.9% oxygen, 0.7% nitrogen and 0.2% hydrogen; Option 8: 25.8% silicon, 49.7% tin, 14.8% carbon, 8.3% oxygen, 1.2% nitrogen and 0.2% hydrogen; Option 9: 24.7% silicon, 49.8% tin, 15.9% carbon, 8.2% oxygen, 1.2% nitrogen and 0.2% hydrogen; Scheme 10: 26.1% silicon, 47.9% tin, 16.2% carbon, 8.5% oxygen, 1.1% nitrogen and 0.2% hydrogen; Scheme 11: 25.9% silicon, 51.9% tin, 13.05% carbon, 8% oxygen, 0.95% nitrogen and 0.2% hydrogen; Scheme 12: 24.7% silicon, 49.9% tin, 16.2% carbon, 7.9% oxygen, 1.1% nitrogen and 0.2% hydrogen; Scheme 13: 27.3% silicon, 50.2% tin, 13.7% carbon, 7.7% oxygen, 0.9% nitrogen and 0.2% hydrogen; Scheme 14: 27.7% silicon, 50.1% tin, 13.1% carbon, 7.9% oxygen, 1% nitrogen and 0.2% hydrogen.
4. The silicon-tin based composite negative electrode material according to any one of claims 1 to 3, characterized in that: The silicon-tin-based composite negative electrode material is prepared by the following method, which comprises the following steps (1) to (4): Step (1): in the presence of an alkali, a solvent and a nitrogen source, a silicon-tin-based material, an alkylated carbon nanotube, a phenolic compound and an aldehyde compound are subjected to a phenolic resin polymerization reaction, and the product is heat-treated to obtain silicon-tin-based@carbon nanotube-doped carbon; Wherein, the mass ratio of the alkylated carbon nanotube to the silicon-tin-based material is (0.12-0.43): 1; The mass ratio of the phenolic compound to the silicon-tin-based material is (0.013-0.047): 1; The mass ratio of the aldehyde compound to the silicon-tin-based material is (3.7-12.9): 1; In the silicon-tin-based material, the mass ratio of silicon element to tin element is 1:(1.5-2.3); Step (2): coating the silicon-tin-based@carbon nanotube-doped carbon with a NiO layer to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO; Step (3): reacting the silicon-tin-based@carbon nanotube-doped carbon@NiO in a solvent in the presence of a surfactant, a nitrogen source and an initiator, and heat-treating the product to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon; Wherein, the mass ratio of the nitrogen source to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (3-1): 1; Step (4): In the presence of an acid, removing NiO from the silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon to obtain the silicon-tin-based composite negative electrode material.
5. The silicon-tin based composite negative electrode material according to claim 4, characterized in that: It meets one or more of the following conditions: (1) In step (1), the base is a strong base or a weak base; the strong base may be sodium hydroxide; the weak base may be sodium carbonate or sodium citrate; the base is preferably sodium carbonate; (2) In step (1), the solvent is water, such as deionized water; (3) In step (1), the nitrogen source is one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobis(ethylbutyronitrile) and pyrrole, for example, p-nitroaniline; (4) In step (1), the phenolic compound is resorcinol; (5) In step (1), the aldehyde compound is formaldehyde; (6) In step (1), the phenolic resin polymerization reaction may also be carried out in the presence of a surfactant, wherein the surfactant is preferably a cationic surfactant, preferably a quaternary ammonium salt cationic surfactant, such as one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, and another example is hexadecyltrimethylammonium bromide or dialkyldimethylammonium chloride; (7) In step (1), the mass ratio of the alkali to the silicon-tin-based material is (0.0002-0.009):1, for example, 0.00029:1 or 0.00024:1; (8) In step (1), the mass ratio of the nitrogen source to the silicon-tin-based material is (0.00024-0.0034):1, for example, 0.0011:1 or 0.001:1; (9) In step (1), the mass ratio of the alkylated carbon nanotubes to the silicon-tin-based material is 0.23:1 or 0.2:1; (10) In step (1), the mass ratio of the phenolic compound to the silicon-tin-based material is 0.03:1 or 0.027:1; (11) In step (1), the mass ratio of the aldehyde compound to the silicon-tin-based material is 7.7:1 or 6.6:1; (12) In step (1), the mass ratio of silicon to tin in the silicon-tin-based material is 1:(1.6-2.1); (13) In step (1), the reaction temperature of the phenolic resin polymerization reaction is 80-100°C, preferably 90°C; (14) In step (1), the reaction time of the phenolic resin polymerization reaction is 2-10 hours, for example 6 hours; (15) In step (1), the heat treatment temperature is 600-700°C, preferably 650°C; (16) In step (1), the heat treatment time is 2-40 hours, for example 10 hours; (17) In step (1), the silicon-tin-based material is preferably prepared by the following steps: drying and heat-treating a sol containing tin and a surfactant, and introducing a silicon source gas by atomic layer deposition to prepare the silicon-tin-based material; (18) In step (1), the alkylated carbon nanotubes are prepared by the following steps: Step A: preparing carbon nanotubes from graphite by an arc method; Step B: Carboxylating the carbon nanotubes in the presence of an acid and potassium permanganate to obtain carboxylated carbon nanotubes; Step C: in the presence of an alkyl alcohol or an alkyl amine, subjecting the carboxylated carbon nanotubes to an alkylation reaction to obtain alkylated carbon nanotubes; (19) Step (2) comprises the following steps: reacting silicon-tin-based@carbon nanotube-doped carbon in a solvent in the presence of a surfactant, a nickel salt, an initiator and a base, and heat treating the product to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO; (20) In step (3), the solvent is water, such as deionized water; (21) In step (3), the surfactant is an anionic surfactant, preferably one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate; preferably hexadecyltrimethylammonium p-toluenesulfonate; (22) In step (3), the nitrogen source is a 5-6 membered heterocyclic compound containing 1, 2 or 3 nitrogen atoms; preferably a 5-6 membered heterocyclic compound containing 1 nitrogen atom; for example, pyridine and / or pyrrole; (23) In step (3), the initiator is a persulfate, preferably one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate, such as potassium persulfate; (24) In step (3), the mass ratio of the nitrogen source to the silicon-tin-based@carbon nanotube-doped carbon@NiO is 2:1; (25) In step (3), the mass ratio of the surfactant to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (0.03-0.1):1, preferably 0.08:1; (26) In step (3), the mass ratio of the initiator to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (2-6.5):1, preferably 3.5:1; (27) In step (3), the reaction temperature is -5-10°C, preferably 0-5°C; (28) In step (3), the heat treatment temperature is 550-850°C, preferably 700°C; (29) In step (3), the heat treatment is carried out under an inert atmosphere, preferably under an argon atmosphere; (30) In step (3), the heat treatment time is 3-10 h, preferably 5 h; (31) In step (4), the acid is an inorganic acid, preferably one or more of hydrochloric acid, nitric acid and sulfuric acid, such as hydrochloric acid; the concentration of the hydrochloric acid is more preferably 5 mol / L; and (32) step (4) may further include a washing and / or drying step; the washing may be washing with deionized water; the drying may be vacuum drying; the vacuum drying temperature is preferably 80°C.
6. The silicon-tin based composite negative electrode material according to claim 5, characterized in that: It meets one or more of the following conditions: (1) In step (1), when the phenolic resin polymerization reaction is carried out in the presence of a surfactant, the mass ratio of the surfactant to the silicon-tin-based material is (0.017-0.069):1, for example, 0.047:1 or 0.04:1; (2) In step (1), the phenolic resin polymerization reaction comprises the following steps: mixing a mixture containing a surfactant, alkylated carbon nanotubes and a solvent with a nitrogen source, a phenolic compound, an aldehyde compound, an alkali and a silicon-tin-based material, and performing a phenolic resin polymerization reaction at 80-100° C.; Wherein, the surfactant, the alkylated carbon nanotubes, the solvent, the nitrogen source, the phenolic compound, the aldehyde compound, the base and the silicon-tin-based material are defined as in claim 5; (3) In step (1), in the method for preparing a silicon-tin-based material, the tin is an inorganic salt of tin, such as tin tetrachloride; (4) In step (1), in the method for preparing a silicon-tin-based material, the surfactant is a cationic surfactant, preferably a quaternary ammonium salt cationic surfactant, such as one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, and for example, hexadecyltrimethylammonium bromide or dialkyldimethylammonium chloride; (5) In step (1), in the method for preparing silicon-tin-based materials, the silicon source gas is one or more of tetraethoxysilane, methylsilane, ethylsilane and silane, preferably methylsilane; (6) In step (1), in the method for preparing silicon-tin-based materials, the flow rate of the silicon source gas introduced is 50-100 mL / min; preferably 60 mL / min; (7) In step (1), in the method for preparing silicon-tin-based materials, the working temperature of the atomic layer deposition in which the silicon source gas is introduced is 100-300°C; preferably 200°C or 250°C; (8) In step (1), in the method for preparing silicon-tin-based materials, the duration of the atomic layer deposition with the silicon source gas introduced is 24-48 hours, preferably 28 hours; (9) In step (1), in the method for preparing a silicon-tin-based material, the number of cycles of atomic layer deposition with the silicon source gas introduced is 50-200; preferably 80 or 120 times; (10) In step (1), in the method for preparing a silicon-tin-based material, the drying temperature is 80-100°C; (11) In step (1), in the method for preparing alkylated carbon nanotubes, the alkyl alcohol is a lower alcohol or a higher alcohol; the lower alcohol may be methanol, ethanol or propanol; the higher alcohol may be lauryl alcohol or stearyl alcohol; the alkyl alcohol is preferably lauryl alcohol; (12) In the method for preparing alkylated carbon nanotubes in step (1), the alkylamine is octadecylamine; (13) In the method for preparing alkylated carbon nanotubes in step (1), the alkylated carbon nanotubes are lauryl alkylated carbon nanotubes or octadecyl alkylated carbon nanotubes; (14) In step (2), the solvent is water, such as deionized water; (15) In step (2), the surfactant is a cationic surfactant, preferably a quaternary ammonium salt cationic surfactant, such as one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, and for example hexadecyltrimethylammonium bromide or dialkyldimethylammonium chloride; (16) In step (2), the nickel salt is an inorganic salt of nickel, such as nickel acetate; (17) In step (2), the initiator is a persulfate, preferably one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate, such as potassium persulfate; (18) In step (2), the base is an inorganic base, such as aqueous ammonia, more preferably 10% (w / w) aqueous ammonia; (19) In step (2), the heat treatment temperature is 350-600°C, preferably 400°C; and (20) step (3) comprises the following steps: mixing the silicon-tin-based@carbon nanotube-doped carbon@NiO, a surfactant, a nitrogen source and an initiator in a solvent, reacting at 0-5°C, collecting the product, drying it, and heat treating it to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon; The mass ratio of the nitrogen source to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (3-1):
1.
7. The silicon-tin based composite negative electrode material according to claim 6, characterized in that: The step (2) comprises the following steps: mixing a mixture containing silicon-tin-based@carbon nanotube-doped carbon and a surfactant, a mixture containing a nickel salt and an initiator, and a base, reacting at room temperature, collecting the product, drying, and heat treating to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO.
8. A method for preparing a silicon-tin based composite negative electrode material according to any one of claims 1 to 7, characterized in that: It includes the following steps (1) to (4): Step (1): in the presence of an alkali, a solvent and a nitrogen source, a silicon-tin-based material, an alkylated carbon nanotube, a phenolic compound and an aldehyde compound are subjected to a phenolic resin polymerization reaction, and the product is heat-treated to obtain silicon-tin-based@carbon nanotube-doped carbon; Wherein, the mass ratio of the alkylated carbon nanotube to the silicon-tin-based material is (0.12-0.43): 1; The mass ratio of the phenolic compound to the silicon-tin-based material is (0.013-0.047): 1; The mass ratio of the aldehyde compound to the silicon-tin-based material is (3.7-12.9): 1; In the silicon-tin-based material, the mass ratio of silicon element to tin element is 1:(1.5-2.3); Step (2): coating the silicon-tin-based@carbon nanotube-doped carbon with a NiO layer to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO; Step (3): reacting the silicon-tin-based@carbon nanotube-doped carbon@NiO in a solvent in the presence of a surfactant, a nitrogen source and an initiator, and heat-treating the product to obtain silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon; Wherein, the mass ratio of the nitrogen source to the silicon-tin-based@carbon nanotube-doped carbon@NiO is (3-1): 1; Step (4): removing NiO from the silicon-tin-based@carbon nanotube-doped carbon@NiO@amorphous nitrogen-doped carbon in the presence of an acid to obtain the silicon-tin-based composite negative electrode material; The steps (1), (2), (3) and (4) are as described in claim 4.
9. Use of the silicon-tin based composite negative electrode material as claimed in any one of claims 1 to 7 in a battery.
10. A battery comprising the silicon-tin-based composite negative electrode material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Monatomic tin-based composite carbon material, and preparation method and application thereof
CN113782732A
Method and system for preparing single / double-walled carbon nanotubes through direct-current arc discharge
CN118343745A